Inflammatory effects of particulate matter air pollution (2020)
Air pollution is an important cause of non-communicable diseases globally with particulate matter (PM) as one of the main air pollutants. PM is composed of microscopic particles that contain a mixture of chemicals and biological elements that can be harmful to human health. The aerodynamic diameter of PM facilitates their deposition when inhaled. For instance, coarse PM having a diameter of < 10 μm is deposited mainly in the large conducting airways, but PM of < 2.5 μm can cross the alveolar-capillary barrier, traveling to other organs within the body. Epidemiological studies have shown the association between PM exposure and risk of disease, namely those of the respiratory system such as lung cancer, asthma, and chronic obstructive pulmonary disease (COPD). However, cardiovascular and neurological diseases have also been reported, including hypertension, atherosclerosis, acute myocardial infarction, stroke, loss of cognitive function, anxiety, and Parkinson's and Alzheimer's diseases. Inflammation is a common hallmark in the pathogenesis of many of these diseases associated with exposure to a variety of air pollutants, including PM. This review focuses on the main effects of PM on human health, with an emphasis on the role of inflammation.